2020
DOI: 10.1007/s12600-020-00831-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dimethoate resistance in Oxycarenus hyalinipennis (Costa): resistance selection, cross-resistance to three insecticides and mode of inheritance

Abstract: Dusky cotton bug Oxycarenus hyalinipennis (Costa) (Hemiptera: Lygaeidae) has been found to infesting cotton and other plants in Pakistan and some other countries. However, in Pakistan the increasing infestation of O. hyalinipennis was controlled with different insecticides, but some degree of resistance has been reported. Inheritance and cross-resistance of dimethoate resistance selection have not been documented in O. hyalinipennis previously. Therefore, this study for the first time characterized dimethoate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Moreover, the D ML levels observed in this study directs that higher doses of Dipel could make resistance incompletely and completely recessive, and so can be employed to minimize the resistance occurrence in E. vittella . The concentration-dependent dominance was also observed in other studies [ 34 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the D ML levels observed in this study directs that higher doses of Dipel could make resistance incompletely and completely recessive, and so can be employed to minimize the resistance occurrence in E. vittella . The concentration-dependent dominance was also observed in other studies [ 34 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 86%
“…The present study indicates that after 11 rounds of sulfoxaflor selection the DCB population showed 1132.0‐fold resistance compared with Lab‐Pop. Intense selection pressure of sulfoxaflor for several generations of DCB possibly led to the removal of susceptible individuals and increased the frequency of resistant individuals in a selected population 80 and was ready for crossing with laboratory susceptible strain which showed lowest LC 50 to sulfoxaflor which indicate that this strain is contrasting to Sulfo‐Sel Pop and both were isogenic (homozygous) 41,50,54 . The field‐collected DCB was moderate resistant to sulfoxaflor as compared to Lab‐Pop, which indicates the presence of a few resistant alleles in the field population that may lead to increased development of resistance in DCB following continuous selection pressure of sulfoxaflor in the laboratory 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Mortality was observed after 72 h of exposure to sulfoxaflor 41,50,53 . The insects were considered lifeless when they showed no movement by touching with a fine camel hairbrush 54 …”
Section: Methodsmentioning
confidence: 99%
“…Resistance development to insecticides also occurs due to changes in metabolic systems and insensitive target sites by point mutation (Damayanthi & Karunaratne, 2005). Low to high levels of resistance to different insecticides, including imidacloprid (104fold) , chlorfenapyr (149.06-fold) (Ullah et al, 2016b), bifenthrin (163.0-fold) (Bilal et al, 2018), (55.64-fold) (Banazeer et al, 2020b), dimethoate (9.70-fold) (Banazeer et al, 2020a), deltamethrin (12-fold), triazophos (5.42-fold), profenofos (39-fold), and lambda-cyhalothrin (6.68-fold) Cross-resistance is the phenomena of development of resistance in insects to unexposed insecticides of related or unrelated groups (Gorman et al, 2010). In our study, selection with spirotetramat induced very low cross-resistance to bifenthrin and no cross-resistance to triazophos and emamectin benzoate, respectively.…”
Section: Discussionmentioning
confidence: 99%